Knowledge of health professionals on nutritional management of obese adolescents in primary health care (Revista Contexto & Saúde, 2025)
This study assessed primary care personnel’s knowledge regarding nutritional management for obese adolescents receiving care in Primary Health Care under Brazilian Unified Health System in Piauí. This descriptive, cross-sectional, quantitative study used data from the Obesity Prevention and Control Program implemented in Primary Health Care under Brazilian Unified Health System in Piauí, conducted between March and October 2021. Health professionals completed two questionnaires: “Knowledge of Nutrition in Obese Adolescents” and “Diagnosis of the Organization, Management, and Nutritional Care Offered to People with Overweight and Obesity in Primary Health Care”. Statistical analyses were performed using Stata version 14. Differences between nutritionists and other health professionals were assessed using the Student’s t-test and the Mann-Whitney U test, with a 5% significance level. Out of 585 primary health care units across the 190 municipalities included in the sample, 183 health professionals participated in the study, the majority being nutritionists (71.58%), public sector employees (41.53%), and working in rural areas (51.91%). Among all participants, 59.02% showed knowledge rated as good or very good. Statistical differences were observed between respondent groups, with dietitians demonstrating higher knowledge regarding general adolescent nutrition in obesity (p=0.000) and across specific questionnaire topics: fruit and vegetable consumption (p=0.010), fat intake (p=0.000), and nutritional management for obese adolescents (p=0.000). The implementation of public policies aimed at the training and ongoing education of health professionals, emphasizing obesity prevention and control, should be encouraged.
Keywords: Obesity Management; Primary Health Care; Health Personnel; Adolescent Nutrition